2006
DOI: 10.1002/lapl.200610110
|View full text |Cite
|
Sign up to set email alerts
|

Internal-loss-limited maximum operating temperature and characteristic temperature of quantum dot laser

Abstract: Carrier-density-dependent internal optical loss sets an upper limit for operating temperatures and considerably reduces the characteristic temperature of a quantum dot laser. Such internal loss also constrains the shallowest potential well depth and the smallest tolerable size of a quantum dot at which the lasing can be attained. At the maximum operating temperature or when any parameter of the structure is equal to its critical tolerable value, the characteristic temperature drops to zero. Minimum tolerable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The carrier-density-dependent internal loss can be presented as n int 0 int σ α α + = (28,29), where α 0 is the constant component (which can be caused by scattering at rough surfaces or absorption in the cladding layers), σ int is the effective cross section for internal absorption loss processes, n is the free-carrier density in the optical confinement layer (OCL), and the component n int σ is caused by free-carrier absorption in the OCL. In the presence of such a loss, the lasing condition is written as (17,28,29) , [1] where g max is the maximum value of the gain (30), f n is the confined-electron level occupancy in QDs, ( ) ( ) R L 1 ln 1 = β is the mirror loss, L is the cavity length, and R is the facet reflectivity.…”
Section: Carrier-density-dependent Internal Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The carrier-density-dependent internal loss can be presented as n int 0 int σ α α + = (28,29), where α 0 is the constant component (which can be caused by scattering at rough surfaces or absorption in the cladding layers), σ int is the effective cross section for internal absorption loss processes, n is the free-carrier density in the optical confinement layer (OCL), and the component n int σ is caused by free-carrier absorption in the OCL. In the presence of such a loss, the lasing condition is written as (17,28,29) , [1] where g max is the maximum value of the gain (30), f n is the confined-electron level occupancy in QDs, ( ) ( ) R L 1 ln 1 = β is the mirror loss, L is the cavity length, and R is the facet reflectivity.…”
Section: Carrier-density-dependent Internal Lossmentioning
confidence: 99%
“…The effect of the n-dependent internal loss in the OCL on the T-dependence of j th was studied in (17). A GaInAsP/InP heterostructure lasing near 1.55 µm and having the following parameters was used for calculations (28,29): the root mean square (RMS) of relative QD-size fluctuations δ = 0.05 (Gaussian distribution was assumed), the OCL thickness b = 0.28 µm, the surface density of QDs N S = 10 10 11 .…”
Section: Carrier-density-dependent Internal Lossmentioning
confidence: 99%
“…With a high J th , the absorption loss caused by the injected carriers in the cavity also cannot be neglected. 21 When the injected current is below threshold, the spontaneous electroluminescence (SE) emission spectra from the laser diodes can also be measured. It was found that with increasing current injection, the SE peak exhibits a blue shift.…”
mentioning
confidence: 99%
“…There can be several mechanisms for internal loss, [1][2][3][4][5][6] such as freecarrier absorption, intervalence band absorption, and scattering at rough surfaces. While there have been studies of the effect of internal loss on the threshold and power characteristics of semiconductor lasers with a quantum-confined active region and, particularly, quantum dot (QD) lasers, [7][8][9] no consideration of the dynamic properties of QD lasers in the presence of internal loss has been given so far. In this work, we study the modulation response of a QD laser taking into account the carrier-density-dependent internal loss in the optical confinement layer (OCL).…”
mentioning
confidence: 99%
“…In the general case, the internal loss coefficient can be presented as [7][8][9] a int ¼ a 0 þ r int n OCL ;…”
mentioning
confidence: 99%